Growth, Employment, Skills and Female Labor Force - Taymaz, Erol (World Bank, Ankara, 2017)
This report is organized as follows. After this introduction, the second section explains the main data sources used in the study. The third section discusses the relationship between sectoral output growth and employment generation, and presents basic estimates on growth elasticities. The fourth and fifth section presents detailed descriptive analyses on the pattern of employment growth. The sixth section summarizes the findings of an econometric analysis on labor market participation decisions, with a special emphasis on female labor, and the determinants of wages. The author estimate the multi-nominal logical model for labor market participation decisions of men and women living in urban regions for each year since 2000, and estimate the wage equation for 2006 by taking into account the labor market participation decision (the sample selection effect). The last section presents the main findings of the study.